The nature of suffering : and the goals of medicine - Cassell, Eric J., 1928-2021 (Oxford University Press, 1994)
The Nature of Suffering underscores the change that is taking place in medicine from a basic concern with disease to a greater focus on the sick person. Cassell centers his discussion on the problem of suffering because, he says, its recognition and relief are a test of the adequacy of any system of medicine. He describes what suffering is and its relationship to the sick person: bodies do not suffer, people do. An exclusive concern with scientific knowledge of the body and disease, therefore, impedes an understanding of suffering and diminishes the care of the suffering patient. The growing c.
Keywords: Medicine -- Philosophy.; Suffering.; Physician and patient.; Chronic Disease -- therapy; Philosophy, Medical; Physician-Patient Relations; Médecine -- Philosophie.; Souffrance.; Relations médecin-patient.; MEDICAL -- Family & General Practice.; MEDICAL -- Osteopathy.; MEDICAL.; MEDICAL -- Holistic Medicine.; HEALTH & FITNESS -- Reference.; MEDICAL -- Essays.; MEDICAL -- Alternative Medicine.; HEALTH & FITNESS -- Holism.; Medicine -- Philosophy; Physician and patient; Suffering